Simple forage evaluation techniques - Mohamed-Saleem, M.A.; Bayer, W. (International Livestock Centre for Africa, 1984)
Presents and discusses some simple forage evaluation techniques. Includes seedling emergence & establishment, yield, growth & utilization, and botanical composition.